Role of T-2 toxin in the modulation of oxidative homeostasis and immune function in three-dimensional hepatic cell cultures of chicken origin - Vörösházi, Júlia; Mackei, Máté; Sebők, Csilla; Tráj, Patrik; Márton, Rege A.; Neogrády, Zsuzsanna; Mátis, Gábor (Frontiers in Veterinary Science, 2026)
T-2 toxin is a secondary metabolite produced by different Fusarium species that causes serious problems in the poultry industry. It can damage several organ systems, mainly by inhibiting protein synthesis, and is also likely to induce oxidative stress in cells. In this study, the adverse effects of T-2 toxin were investigated in magnetic three-dimensional hepatic cell cultures of chicken origin. Cultures were treated with 100, 500, and 1,000 nM T-2 toxin for 48 and 72 h. The metabolic activity of the cells was determined using CCK-8 assay. To investigate the changes in the oxidative homeostasis, the levels of MDA, HSP27, and 8-OHdG were measured. To monitor immune response, the concentrations of IL-6 and 8 were determined. The metabolic activity of the cells decreased after the toxin treatments, but this decrease was alleviated after 72 h. Both MDA and HSP27 levels were significantly diminished by T-2 toxin after 48 h. The concentration of 8-OHdG was reduced by 72 h exposure to 100 nM T-2 toxin. In the case of IL-6, the 1,000 nM T-2 toxin was able to decrease its levels after 48 and 72 h, whereas IL-8 levels were lowered after 72 h by all three toxin treatments. Overall, these results suggest that T-2 toxin had a negative effect on the cell function of the hepatic spheroids, but it was not cytotoxic. The cells showed metabolic adaptation to the 72 h treatment and possessed effective compensation against oxidative stress while eliciting an immunosuppressive effect on the liver cells. These findings indicate that subclinical T-2 toxin exposure may impair liver metabolism and the immune system in poultry, highlighting the importance of regular mycotoxin monitoring and elimination techniques from the feed.